Singular Pertubations in Systems and Control - Kokotović, Petar (IEEE, 1986)
Contiene ensayos sobre los siguientes temas: singular pertubations; mathematical background; stability and robustness; modeling of large scale systems; nonlinear optimal control; linear optimal control; feedback control; stochastic systems.